KARAKTERISTIK TOKOH DAN NILAI PENDIDIKAN PADA WAWACAN ALADIN SUNTINGAN RANY FEBRIANI UNTUK BAHAN AJAR BERBASIS KARAKTER DI TINGKAT SMA/SMK/MA - Siti Nur’azizah; Rany Febriani (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2017)
The background of this research is the lack of society’s knowledge and reading interest in Wawacan. The purposes of this research are to describe, to analyze, and to unvestigate the karakteristik tokoh and the educational values in Wawacan Aladin that onward will be arranged design material character wawacan based inSMA/SMK/MA. Source data from this research is Wawacan Aladin written by Sastera and edited by Rany Febriani. This research used analythical descriptive method. Technique are used in this research is the literature technique. According to the study, Wawacan Aladin told about life and walk aladin accompanied jimatfigures. The Structure Wawacan Aladin has a mix storyline, there are five motifs of the story, the first character in Wawacan Aladin is Aladin, the background of story background includes spaces, time, and social, as well as the theme of the story in Wawacan Aladin is kepemimpinan. There are 28 kantos from 12 pupuh and 550 padas used in Wawacan Aladin. Seen from the built that figure is 28.Characteristic of the characters covering positive and negative character.The positive character seen from a figure inWawacan Aladin analyzed to be an education value of them: 1) The education value in His Lordcharacter2) The education value to himself character, of them: (1) Honest character, (2) Responsible character, (3) Discipline character, (4) Hardworking character, (5) Confident character, (6) Logical and critical character, (7) Autonomous character, (8) Curiosity character, (9) Love saince, 3) Theeducation value on one another character, including: (1) aware of rights and obligations, (2) obey the social, (3) appreciate work and accomplishments, (4) manners, and (5) democratic, 4) The educationvalue in his people with him tolerance.